2011
DOI: 10.1038/oby.2011.176
|View full text |Cite
|
Sign up to set email alerts
|

Serum Amyloid A Induces Lipolysis by Downregulating Perilipin Through ERK1/2 and PKA Signaling Pathways

Abstract: Serum amyloid A (SAA) is not only an apolipoprotein, but also a member of the adipokine family with potential to enhance lipolysis. The purpose of this study was to explore how SAA facilitates lipolysis in porcine adipocytes. We found that SAA increased the phosphorylation of perilipin and hormone‐sensitive lipase (HSL) after 12‐h treatment and decreased perilipin expression after 24‐h treatment, and these effects were prevented by extracellular signal‐regulated kinase (ERK) or protein kinase A (PKA) inhibitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 40 publications
3
31
0
Order By: Relevance
“…Mutations in perilipin have been recently shown to increase lipolysis because of failing to sequester the interaction between ATGL and CGI-58 (Gandotra et al, 2011).It has been shown in perilipin null mice that basal lipolysis is elevated and the size of adipocytes is smaller (Martinez-Botas et al, 2000;Tansey et al, 2001). And a number of studies have demonstrated that increase (decrease) of perilipin via overexpression (gene knock-down) or hormonal/chemical stimulation (inhibition) results in reduced (increased) lipolysis and increased (reduced) lipid droplet size (Souza et al, 1998;Tansey et al, 2004;Sawada et al, 2010;Liu et al, 2011a).…”
Section: Discussionmentioning
confidence: 97%
“…Mutations in perilipin have been recently shown to increase lipolysis because of failing to sequester the interaction between ATGL and CGI-58 (Gandotra et al, 2011).It has been shown in perilipin null mice that basal lipolysis is elevated and the size of adipocytes is smaller (Martinez-Botas et al, 2000;Tansey et al, 2001). And a number of studies have demonstrated that increase (decrease) of perilipin via overexpression (gene knock-down) or hormonal/chemical stimulation (inhibition) results in reduced (increased) lipolysis and increased (reduced) lipid droplet size (Souza et al, 1998;Tansey et al, 2004;Sawada et al, 2010;Liu et al, 2011a).…”
Section: Discussionmentioning
confidence: 97%
“…However, the precise mechanisms that stimulate lipolysis in LS adipocytes remain to be established. Interestingly, one may hypothesize that the observed enhanced insulin-evoked MAPK activation in LS adipose tissue can sustain lipolysis, because MAPK can downregulate perilipin and activate HSL (35,36). Second, beyond an intrinsic effect on adipose tissue maintenance, reduced adiposity and DIO resistance of LS mice is also certainly due, at least in part, to their increased energy expenditure.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a recent study reported that serum amyloid A stimulated lipolysis in parallel with a reduced HSL protein content. However, serum amyloid A caused a signifi cant increase of PKA-mediated HSL phosphorylation ( 44 ), suggesting opposite trends in HSL able to stimulate lipolysis, suggesting that the lipolytic actions are independent of the antioxidant capacities. Our data showed that despite the stimulatory effects of LA on lipolysis, HSL and ATGL gene expression and protein levels were inhibited after 24 h of LA treatment, together with a decrease in perilipin mRNA levels.…”
Section: Effects Of La Treatment On Hsl Atgl Perilipin Cgi-58 Andmentioning
confidence: 99%